Analysis of risk factors for serous exudation of biodegradable material calcium sulfate in the treatment of fracture-related infections - Du, Bing; Su, Yu; Li, Dongchen; Ji, Shuai; Lu, Yao; Xu, Yibo; Yang, Yanling; Zhang, Kun; Li, Zhong; Ma, Teng (Frontiers in Bioengineering and Biotechnology, 2023)
Objective : To explore the related risk factors of serous exudation after antibiotic-loaded calcium sulfate treatment of fracture-related infections and to provide a theoretical basis for clinical treatment and prevention of serous exudation complications. Results : The clinical data of 145 patients with limb fracture-related infection treated with antibiotic-loaded calcium sulfate in Xi 'an Honghui Hospital from January 2019 to December 2022 were retrospectively analyzed. All patients were diagnosed with fracture-related infection by preoperative magnetic resonance examination, bacterial culture and gene detection and received antibiotic-loaded calcium sulfate implantation. The postoperative serous exudation was recorded through hospitalization observation, outpatient review or follow-up. The collected clinical data were sorted out, and the patient data were divided into serous and non-exudation groups. Firstly, the clinical data of the two groups were compared by single-factor analysis to screen out the risk factors. Then multivariate binary Logistic regression analysis determined the independent and protective risk factors. Conclusion : 1. The probability of serous exudation in patients with fracture-associated infection after antibiotic-loaded calcium sulfate surgery was 18.62 %. This complication may cause a heavier economic and psychological burden on patients; 2. With the increase of bone infection area and the application of more calcium sulfate, the incidence of serous exudation after antibiotic-loaded calcium sulfate surgery in patients with the fracture-related infection will increase, so we should use the amount of calcium sulfate reasonably on the premise of sufficient control of infection in clinical work, and the incidence of serous exudation will also increase due to the recent skin flap surgery and the thinner soft tissue coverage of calcium sulfate implantation area ; 3. Under the premise of being able to drain the drainage from the surgical area, the longer drainage time of the drainage tube has a positive effect on preventing the occurrence